THREE IMPROVED METHODS FOR COCONUT OIL EXTRACTION - Suhardiyono; Y.B. Che Man; B.A. Asbi; M.N. Azudin (International Coconut Community, 1993)
Three methods for coconut oil extration using acetic acid, baker's yeast, and mixed enzymes were investigated. Coconut milk was allowed to settle for two hours; for cream separation. When the cream reacted with 25 % acetic acid at 0.l % ‑ 0.4 % levels or baker's yeast at 0.5 ‑ 2 g levels for 10 ‑ 14 hours, the oil was separated into two phases; the upper phase containing coconut oil‑rich fraction and the lower phase consisting of water. The oil phase was finally boiled for 20 minutes to remove moisture. The other extraction method was based on the combined action of cellulase, a ‑amylase, protease, and poly‑galacturonase at 0.1 % to 1 % on grated coconut meat at pH 4 to 8, 400C to 600C for 30 minutes. Oil recovely, moisture content, FFA, peroxide value, saponification value, anisidine value, iodine value and colour of the oil were studied. Up to 60 % recovery of high quality oil was obtained by acetic acid or baker's yeast treatment whilst that of mixed enzymes treatment was 73 %. These three alternatives wet processing showed significant improvement as compared to the traditional process.